Programmable Oil/Water Separation Meshes: Water or Oil Selectivity Using Contact Angle Hysteresis. Issue 9 (8th June 2016) - Dunderdale, Gary J.; England, Matt W.; Sato, Tomoya; Urata, Chihiro; Hozumi, Atsushi
Abstract : Stainless steel meshes, functionalized with amphiphilic copolymer brushes, exhibit large contact angle hysteresis (CA hysteresis) at the oil/water contact line. This CA hysteresis allows the meshes to be programmed to act as either a water‐selective or an oil‐selective filter during oil/water separation. In both program modes, high filtrate purities can be realized (>99%). Abstract : We report a novel method for oil/water separation using stainless steel meshes functionalized with amphiphilic copolymer, poly(methacrylic acid‐ co ‐ethylhexylmethacrylate) (PMAA‐ co ‐EHMA), brushes. Because the PMAA‐ co ‐EHMA brush‐covered surfaces show a large contact angle hysteresis at the oil/water contact line, the meshes can be programmed to act as either water‐selective or oil‐selective filters simply by pre‐wetting the mesh with one of these liquids. These programmable meshes can separate oil/water mixtures to high filtrate purities (more than 99 % mol/mol) in both oil‐selective and water‐selective modes.